PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN PERTAMBANGAN DI BEI - FERDIANA, NORMA (Universitas Katolik Widya Mandala Surabaya, 2012)
Good Corporate Governance is a system for companies to run better working system. The purposes of a company are to earn good profit, to be trusted by stakeholders,and to develop the business properly, so it is necessary to perform well. Company's financial performance can be reviewed in the financial statements. This study aims to determine the effect of good corporate governance to financial performance. The independent variable studied is good corporate governance index, while the dependent variable is financial performance as measured by financial ratios, namely Leverage Ratios, Liquidity Ratios, Efficiency or Turnover or Asset Management Ratios, Profitability Ratios, and Market Value Ratios. The object of this study is a mining company listed on the Indonesia Stock Exchange in 2005- 2010. The samples used are nine mining companies which are selected through purposive sampling. The data is analyzed using regression techniques. The result shows that Good Corporate Governance does not affect all financial ratios. Good Corporate Governance affects Liqudity Ratios, but has no effect on Leverage Ratios, Efficiency or Turnover, or Asset Management Ratios, Profitability Ratios, and Market Value Ratios.